Causes of School Dropout in Topporeng Village, Mallusetasi Sub-District - ., Nismawati; Kamaruddin, Syamsu A.; Said Ahmad, M. Ridwan (KnE Social Sciences, 2024)
This study aims to explore information, discuss, and provide an overview of the causes of school dropouts in Topporeng Village, Mallusetasi Sub-District seen from the following perspective: (1) interest in going to school, (2) the economic condition of dropouts, and (3) the environment where children drop out of school. This type of research is descriptive qualitative research, where the informants taken as samples are school dropouts, and the selection of informants using a purposive sampling technique. The data collection techniques used are observation, interview, and documentation techniques. The analysis technique used was data display, data reduction, data presentation, and conclusion drawing. The results showed that the factors that cause children to drop out of school are: (1) low interest in learning, while on the other hand, the teacher’s method is less varied in teaching, so they do not understand. Also, the teacher gives a lot of assignments and children don’t do them because they don’t understand, (2) low parental income ranging from Rp 300,000-Rp 1,000,000 per month with the main job being farming and dependents between 2-5 people, and (3) the influence of peers, invitations from peers for playing which makes them skip school until they finally drop out of school. Keywords: education, school dropout, economy, social environment 1